Investigation Of The Psychological Effects Of Social Media Use Among Students In Minnesota, United State America - Toyosi Motilola Olola; Akpan Ubong-Abasi Asukwo; Funmilayo Odufuwa (Matondang Journal, 2023)
The study looked into the psychological effects of social media use among students in Minnesota, USA. Specifically, the study assessed the various psychological effects of social media on students in Minnesota and the United States of America. It investigated the impact of social media use on the psychological well-being of students in Minnesota, United States of America. The study adopted a descriptive survey research design. The sample for the study consisted of two hundred (200) students that were randomly selected using a simple random sampling technique. One research instrument tagged "Psychological Effects of Social Media Questionnaire" (PESMQ) was used to collect data for the study. The data collected were analysed using frequency counts and simple percentage analyses of covariance (ANCOVA). According to the study's findings, the psychological effects of social media use among students in Minnesota, United States of America include depression, stress, anxiety, emotional isolation, low self-esteem, memory loss, and self-harm. ca. The study's findings also revealed that the use of social media had a significant impact on the psychological well-being of students in Minnesota, United States of America. The study concluded that depression, stress, anxiety, emotional isolation, low self-esteem, memory loss, and self-harm are the psychological effects of social media use among students and that there is a significant effect of the use of social media on the psychological well-being of the students in Minnesota, United States of America.